FSTL1 accelerates nucleus pulposus-derived mesenchymal stem cell apoptosis in intervertebral disc degeneration by activating TGF-β-mediated Smad2/3 phosphorylation - Xu Yan; Jing-Yu Ding; Ren-Jie Zhang; Yan-Xin Wang; Lu-Ping Zhou; Hua-Qing Zhang; Liang Kang; Chong-Yu Jia; Xiao-Ying Liu; Cai-Liang Shen (Journal of Translational Medicine)
Abstract Background Intervertebral disc degeneration (IVDD) is the leading cause of low back pain, and repair using nucleus pulposus-derived mesenchymal stem cells (NP-MSCs) represents a promising therapeutic approach. However, both endogenous and transplanted NP-MSCs demonstrate limited proliferative capacity, increased apoptosis, and reduced resilience to the harsh microenvironment within the degenerative intervertebral disc (IVD). Methods RNA sequencing (RNA-seq) was utilized to identify genes and associated mechanisms that mediate the responses of NP-MSCs to acidic conditions. Western blotting, qPCR, and immunofluorescence were used to evaluate follistatin-like 1 (FSTL1) expression in NP-MSCs. Apoptosis and extracellular matrix (ECM) anabolism were assessed via flow cytometry, TUNEL staining and Western blotting, while the TGF-β/Smad2/3 pathway was analyzed using Western blotting and immunofluorescence. FSTL1 knockdown with small interfering RNA (siRNA) was performed to determine its role in apoptosis and ECM regulation. The FSTL1 siRNA pretreatment was assessed in a puncture-induced rat IVDD model using MRI and histological staining. Results Using RNA-seq, we identified FSTL1 as the primary acid-responsive gene in NP-MSCs. We further observed elevated FSTL1 expression in NP-MSCs isolated from degenerative IVDs in both humans and rats compared to normal IVDs. Acidic conditions upregulated FSTL1 expression in NP-MSCs in a pH-dependent manner. Notably, recombinant FSTL1 was shown to enhance cellular apoptosis and disrupt ECM metabolism. Conversely, silencing FSTL1 with siRNA reduced NP-MSC apoptosis and improved ECM anabolism. Importantly, TGF-β pathway inhibition partially reversed the pro-apoptotic and ECM catabolism effects of FSTL1. In the rat model of IVDD, pretreatment of NP-MSCs with FSTL1 siRNA significantly suppressed IVDD progression. Conclusions This study provides novel insights into the mechanistic role of FSTL1 in acid-induced apoptosis of NP-MSCs and its contribution to the progression of IVDD. These findings offer valuable perspectives for developing targeted therapeutic strategies to mitigate IVDD progression.